STUDY OF ECOTOURISM PRINCIPLES APPLICATION IN MANAGING NATURE-BASED TOURISM IN THE IJEN CRATER NATURAL PARK - Fitriawati
The existence of tourism designation and conservation functions in natural tourism parks (NTP) raises the need for the concept of NTP management that can accommodate both of these. The concept for organizing tourism in NTP should be sustainable such as ecotourism rather than nature-based tourism in general. One of the well-known tourist destinations is Ijen Crater NTP, Banyuwangi Regency. The development is still being carried out to make Ijen Crater become iconic and able to accelerate the regional and national economy. The attraction of world-class Ijen Crater, coupled with intensive development has the potential to increase the number of visitors continuously. This condition not only has positive impacts but also has the potential for negative impacts on nature, social and local culture if it is not managed properly. Therefore, the principles of ecotourism must be implemented in the Ijen Crater NTP. This study evaluates the application of the principle of ecotourism in the Ijen Crater, which is divided into the principle of natural and cultural conservation, the principle of local’s socio-economic improvement, and the principle of environmental education. In addition, this research also elaborates the compatibility of ecotourism to be applied in NTP. This study uses a qualitative approach. The primary data collection methods used are in-depth interviews and observations, while secondary data are collected through agency document reviews.